Atmospheric rivers in changing climate - Beate G Liepert (Environmental Research Letters, 2013)
Atmospheric rivers are impressive, intermittent circulation features in mid-latitude regions of the globe that can cause disastrous floods if they smash against mountainous terrain. While discovered by meteorologists and long feared by hydrologists they have only recently come to the broader attention of climate scientists. In a new letter published in Environmental Research Letters , Lavers et al (2013 Environ. Res. Lett. 8 034010) investigate atmospheric rivers reaching the British Isles in the context of climate change. They consider these potentially devastating meteorological features in present and future climate model scenarios, and walk through possible mechanisms that could cause them to strengthen. This is a refreshingly new work that estimates extreme events in future climates with an impact driven approach.